Combination of searches for heavy resonances decaying into bosonic and leptonic final states using 36fb −1 of proton-proton collision data at √ s = 13 TeV with the ATLAS detector - Aaboud, M. (2018)
Searches for new heavy resonances decaying into different pairings of W, Z, or Higgs bosons, as well as directly into leptons, are presented using a data sample corresponding to 36.1 fb−1 of pp collisions at √ s = 13 TeV collected during 2015 and 2016 with the ATLAS detector at the CERN Large Hadron Collider. Analyses selecting bosonic decay modes in the qqqq, ννqq, `νqq, ``qq, `ν`ν, ``νν, `ν``, ````, qqbb, ννbb, `νbb, and ``bb final states are combined, searching for a narrow-width resonance. Likewise, analyses selecting the leptonic `ν and `` final states are also combined. These two sets of analyses are then further combined. No significant deviation from the Standard Model predictions is observed. Three benchmark models are tested: a model predicting the existence of a new heavy scalar singlet, a simplified model predicting a heavy vector-boson triplet, and a bulk Randall–Sundrum model with a heavy spin-2 Kaluza–Klein excitation of the graviton. Cross-section limits are set at the 95% confidence level using an asymptotic approximation and are compared with predictions for the benchmark models. These limits are also expressed in terms of constraints on couplings of the heavy vector-boson triplet to quarks, leptons, and the Higgs boson. The data exclude a heavy vector-boson triplet with mass below 5.5 TeV in a weakly coupled scenario and 4.5 TeV in a strongly coupled scenario, as well as a Kaluza–Klein graviton with mass below 2.3 TeV.